2017
DOI: 10.5902/2236130827003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of experimentation in the teaching of sciences to elementary school

Abstract: A experimentação, principalmente se comunicativa, é importante fator contribuinte para o interesse e a aprendizagem significativa em Ciências. Deste modo, o presente trabalho reconhece a importância da inserção da experimentação de maneira problematizadora no ensino de Ciências no nível fundamental, bem como realiza uma revisão sobre o assunto utilizando-se de artigos, leis, parâmetros e programas nacionais, e como os mesmos referemse ao Livro Didático e ensino fundamental ligados à experimentação. Com isto, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The teacher facilitates teaching by motivating students to explore new ideas, pose interesting questions (Beuermann et al, 2013), and to apply their knowledge in novel situations. Continuous teacher training is necessary so that the teacher is able to innovate in classes, stimulate students' motivation and interest by applying theory and practice, so that students better assimilate the content, relating it to their everyday lives (Soares et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher facilitates teaching by motivating students to explore new ideas, pose interesting questions (Beuermann et al, 2013), and to apply their knowledge in novel situations. Continuous teacher training is necessary so that the teacher is able to innovate in classes, stimulate students' motivation and interest by applying theory and practice, so that students better assimilate the content, relating it to their everyday lives (Soares et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A series of activities need to be carried out in the classroom with the aim of strengthening motivation and learning life skills such as creative problem solving, critical and divergent thinking, logical connection, and quite importantly, encouraging students' independence in learning and practical tasks. It is of great importance to raise awareness in natural science teachers that experiment arouses students' interest at different levels of learning because experiment increases learning ability by including students in topics covered during the educational process (Soares et al, 2016). According to a report to the European Commission (Rocard et al, 2007), research-based learning holds great benefits and has been shown to increase student interest and educational accomplishments at primary and secondary levels, while having a positive effect on teacher motivation.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental teaching method, investigations are involved in which hypotheses are scientifically tested. A straightforward and entertaining framework for introducing students to quantitative social research is provided via experiments (Soares et al, 2016). According to Soares et al (2016), this lesson plan could be used as a guide to teach students how to conduct more difficult research.…”
Section: Experimentation Methodsmentioning
confidence: 99%
“…Penerapan metode eksperimen ini memberikan kemudahan pada siswa dalam memahami materi yang diberikan guru, melalui penemuannya sendiri, dimana manipulasi lingkungan serta adanya pengalaman-pengalaman fisik akan memberikan pengaruh dalam perubahan perkembangan kognitif siswa (Price & Brooks, 2012). Keterlibatan siswa dalam semua fase pembelajaran juga dapat meningkatkan pemikiran dan kreasi sehingga dapat membangun pembelajaran yang terus menerus dan bermutu.Siswa juga lebih tertarik dan semangat dalam mengikuti pelajaran (Soares et al, 2016). Hal ini didukung dari hasil angket yang disebar pada akhir pembelajaran dimana siswa memberikan respon positif terhadap pembelajaran IPA yang menerapkan metode eskperimen tersebut.…”
Section: Hasil Belajar Siswaunclassified